Ulama Pesantren dan Upaya Penanggulangan Radikalisme di Indonesia - Rosidin, Rosidin; Arfan, Iklil Athroz (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
The concepts of jihad, heresy, and Khilafah, as interpreted by transnational radical groups, have contributed to many conflicts in Indonesia. The objective of this article is to provide an in-depth examination of the strategies employed by the eight Rais Aam Syuriah and four General Chairmen of the Nahdlatul Ulama (PBNU) in countering radicalism in Indonesia. This article employs a qualitative approach and a literature review methodology. The article presents three findings. Firstly, the process of deradicalization through an intellectual approach is achieved through an understanding of religious knowledge from authoritative Islamic scholars, verified literature, and complex methods of legal extraction. This is employed to produce contextual legal fatwas, which serve as a solution to the textual legal fatwas of radical groups. Secondly, deradicalization through a cultural approach is conducted continuously to harmonize religion and culture through various approaches. The cultural approach represents a solution to the cultural resistance exhibited by radical groups. Thirdly, deradicalization through a constitutional approach is directed at educating for nationalism, Pancasila, the trilogy of brotherhood, and a critical review of the 1945 Constitution and its derivatives. The constitutional approach represents a solution to the radical movement that seeks to alter the fundamental tenets of the four pillars of nationalism in favor of their ideological framework.